Study on Aligning E-Learning and Knowledge Maturity for Institutional Success: - (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The maturity model derives from the principles of the Capability Maturity Model (CMM) of software e-learning maturity model is a framework for quality improvement to apply the e-learning. The purpose of this research is to apply the eMM to identify strengths and weaknesses and to prepare recommendations for improvement for e-learning. This research presents a commitment to the e-learning maturity model (eMM) with the fuse of a new Key Process Area the Accessibility. This model will be applied to an India Higher Education Institution, with interesting results.